Color stability of glass ionomer-based restorative materials after immersion in various beverages - Manopetchkasem, Apichaya; Kannasombat, Arissara; Charumattanont, Pribdao; Charoonmethee, Tisthong; Suriyasangpetch, Sarat (Mahidol Dental Journal, 2024)
Objective: The aim of this study was to evaluate the color stability of various glass ionomer-based restorative materials after immersion in different acidic beverages over multiple time points. Materials and Methods: Four restorative materials (n = 36) were tested: conventional glass ionomer (Fuji IX), resin-modified glass ionomer (Fuji II LC), zirconomer (Zirconomer Improve), and giomer (Beautifil X). Specimen discs were fabricated and their baseline color was measured using a spectrophotometer. The specimens were then immersed in one of four media (n = 9): grape juice (pH 3.50), cola (pH 2.67), chocolate milk (pH 6.99), or distilled water (pH 5.97) as a control. The immersion periods were 1 hour, 1 day, and 1 week, with the solutions changed daily. Color measurements were taken at each time point using the CIEDE2000 color system to calculate the color change (ΔE00). Results: Immersion in grape juice and cola resulted in significantly higher color changes across all materials compared with chocolate milk and distilled water. After one week, cola induced substantial color alterations in all materials, while grape juice yielded notable changes in most materials except Zirconomer Improve. Fuji II LC and Fuji IX exhibited significant color differences when immersed in grape juice at all time points. Distilled water and chocolate milk exerted minimal effects on color stability. Conclusions: Immersion in grape juice and cola significantly altered the color across materials, with cola inducing substantial changes after one week and grape juice notably discoloring most materials, except Zirconomer Improve. Fuji II LC and Fuji IX showed significant discoloration from grape juice exposure.